Parents’ attitudes towards domestic violence from their point of view in the Prince Hassan Primary School of the First Zarqa District - Barghoth, Maysaa Majed (Journal of Educational and Psychological Sciences, 2022)
The aim of this research is to identify the attitudes of parents towards domestic violence from their point of view in the Prince Hassan neighborhood school in Zarqa. He adopted the descriptive approach using a random sample, and applied a questionnaire tool, which consisted of (150) parents of the school’s students, and the number of students was (300). Data were collected from the members of the research sample by means of a questionnaire consisting of (20) phrases. The tool was divided into three areas: the educational level of the family, socialization, the school environment and its role in violence, and it covered the behavioral dimensions of this research. The research found that there are effects of domestic violence against children that are attributed to the variable of the educational level of the parents, and that there are factors of family violence against children that are attributed to the field of socialization, and the existence of factors of family violence that are attributed to the field of the school environment. Based on the results of this research, the researcher recommended that the Ministry of Education take the phenomenon of violence into consideration to find solutions to this phenomenon and the importance of conducting more studies on the issue of domestic violence against children. And the search for the impact of other variables on domestic violence against children.